Description and phylogenetic position of three new species of Stauroneis Ehrenberg (Bacillariophyceae: Stauroneidaceae) from the Indian Subcontinent. Issue 1 (2nd January 2022) - Wadmare, Neha; Baghela, Abhishek; Kociolek, John Patrick; Karthick, Balasubramanian
ABSTRACT: Stauroneis Ehrenberg is a species-rich genus that is common and widespread with some variation in frustule morphology. Recently, studies have explored the molecular diversity of the Stauroneis from the temperate region, but there are no molecular data for tropical species. In the present study, four species of Stauroneis were investigated using morphological and molecular data. Morphological characters were analysed using light microscopy (LM) and scanning electron microscopy (SEM), and the features of each taxon were compared with similar species within the genus. For the molecular analyses, Stauroneis strains were isolated, cultured, DNA was extracted, and sequences from rbc L and 18S genes were analysed to determine phylogenetic relationships. Our analysis describes three new species and records one previously known species. The new species are: (1) Stauroneis lateritica Wadmare, Kociolek & B.Karthick, characterized by small frustules with elliptical lanceolate valves and short subrostrate apices, broad central bow-tie shaped stauros, and few moderate striae centrally becoming strongly radiate towards the poles; (2) Stauroneis sholaii Wadmare, Kociolek & B.Karthick, which has broad lanceolate valves with short rectangular stauros and radiate striae; and (3) Stauroneis bartii Wadmare, Kociolek & B.Karthick, which has large, lanceolate valves with rounded apices, a stauros with 4–7 shortened striae and radiate striae. Ultrastructure and molecular data from India for the previously known, widespread species Stauroneis gracilis Ehrenberg are presented. The combined morphological and molecular approach supports recognition of S. lateritica, S. sholaii and S. bartii as new species. This study is the first-ever attempt at molecular species discovery of diatoms from the Indian subcontinent.